CISD1 in association with obesity‐associated dysfunctional adipogenesis in human visceral adipose tissue. (January 2016) - Moreno‐Navarrete, José María; Moreno, María; Ortega, Francisco; Sabater, Mònica; Xifra, Gemma; Ricart, Wifredo; Fernández‐Real, José Manuel
Abstract : Objective: To investigate CISD1 mRNA and protein in human adipose tissue in association with obesity and adipogenesis. Methods: Subcutaneous (SAT) and visceral (VAT) adipose tissue CISD1 gene expression (real‐time PCR) and protein (Western blot) levels were investigated in human adipose tissue and during human adipocyte differentiation. Results: SAT and VAT CISD1 mRNA and protein levels were significantly decreased in subjects with obesity and negatively correlated with BMI after controlling for age and sex. In participants with morbid obesity, VAT CISD1 gene expression was positively correlated with insulin sensitivity ( r  = 0.47, P  = 0.01), and bariatric surgery‐induced weight loss led to increased SAT CISD1 mRNA levels. In both VAT and SAT, CISD1 gene expression was significantly associated with SIRT1, ISCA2, and mitochondrial biogenesis‐related ( PPARGC1A, TFAM, and MT‐CO3 ) and browning‐related ( PRDM16 and UCP1 ) gene expression. In addition, VAT CISD1 gene expression was significantly associated with adipogenic and iron metabolism‐related genes. Importantly, these correlations were replicated in a second cohort. At the cellular level, CISD1 gene expression increased during human adipocyte differentiation in correlation with adipogenic genes ( r  > 0.60, P  < 0.005). Conclusions: These data suggest a possible role of CISD1 in obesity‐associated dysfunctional adipogenesis in human VAT.